PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP RESPON DAN HASIL BELAJAR PESERTA DIDIK BIOLOGI KELAS VIII SMP NEGERI 55 HALMAHERA SELATAN - Marsaoly, Najamudin; Jufri, Wa Ayu (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research aims to improve the responses and learning outcomes of Class VIII Science students at SMP Negeri 55 South Halmahera by implementing the Numbered Head Together (NHT) Cooperative Learning Model. The procedure for this research is classroom action research which consists of planning, implementation, observation and reflection stages. This classroom action research was carried out in the odd semester of the 2024/2025 academic year in Class VIII of SMP Negeri 55 South Halmahera. From the research results, the students' responses were positive. The average score of the student response questionnaire increased from 7 students stating strongly agree (SS), 11 students stating agree (S) and 2 students stating they were unsure (RR) there was an increase to 15 students stating strongly agree (SS ), 5 students said they agreed (S) and no students said they were doubtful (RR). An increase also occurred in student learning outcomes from 20% in cycle I to 95% in cycle II. Thus, the Numbered Heads Together (NHT) cooperative learning model can improve student responses and learning outcomes.